Building the Test of Drawing Skill for the Female students of Kindergartens' Department - الطاف ياسين الراوي هند لؤي عبد الحميد (College of Education for Women, 2019)
The research issue and its importance concentrate on the importance of choosing and preparing the kindergarten's teacher educationally ,psychologically and artistically ,and other aspects because of their need for several skills such as the drawing skill for kindergarten curriculums include a various artistic experiences and activities as well as for the drawing importance for the child .And from this, the research goals raise from to prepare a test that measures the drawing skill for kindergarten students and measure the drawing skill in all four kindergarten students at the kindergarten department and recognize the differences level for these students . In order to achieve the first goal in the research ,the researchers builds a test for drawing skill in accordance with the artistic expression activities in kindergarten .And the truth and the analytic statistician ( recognition ,the relationship of item degree with the total degree ,the difficulty parameter and stability) so a sample construction amounted (300) female students from kindergartens' department\University of Bagdad\College of education for girls and Mustansiriya University College of basic education, and then had been calculated and applied on a sample of (100) female student in kindergarten students .The results showed that the degree of drawing skill level was medium in female students ,and the third stage students were better than other stages in drawing skill .Thereby ,the test appears in its final form which includes : the drawing skill test , human shape ,cat ,palm tree ,and car, during a specific time (13) minute, while the correction standard was as follows: 1. Each sub-skills in less than specific time given degree (1) 2. Sub skills less in time or less or more than the specified time given degree (zero)